SEISMIC ENERGY DEMAND IN STEEL MOMENT FRAMES - Shen, J.; Akbaş, Bülent (Taylor & Francis Ltd, 1999)
The present paper investigates the seismic energy demand in steel moment-resisting frames. The frames, with 3, 6 and 10 storeys, and 4 and 8 spans, are designed according to current seismic code provisions. The energy response (energy quantities and their distributions) in the frames subjected to an ensemble of six earthquake ground motions recorded on different soil conditions, is investigated by nonlinear time history analysis. The study condudes that (1) the results of energy response can be developed into a rational method of seismic evaluation and design for steel moment-resisting frames; (2) the energy concept based on the single-degree-of-freedom has limitations when extended to the realistic structural system for design purposes; and (3) it is necessary to develop the energy-based approach for seismic evaluation and design based on the seismic response of a realistic multi-degree-of-freedom structural system.
Keywords: seismic energy demand; hysteresis energy distribution; steel frames; nonlinear seismic response